CORONARY ANGIOPLASTY IN MULTIVESSEL DISEASE: REAL-LIFE INSIGHTS AND CLINICAL IMPLICATIONS - Farid Ullah1, Anurag Rawat2, Dr. Fatima Tariq 3, Bryan O. Oyarebu4, Goodness Ebere Onyeukwu5, Huzifa Abdalla Abdelrahman Ahmed6, Dr. Asmat Mustafa Memon7, Shireen Farrukh8 (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
The study evaluates medium-term outcomes of coronary angioplasty in patients with multivessel coronary artery disease (CAD) in real-life conditions. While coronary artery bypass grafting (CABG) has been the gold standard for severe multivessel lesions, advancements in technology and pharmacology have made angioplasty a viable option. Functional revascularization, guided by fractional flow reserve (FFR), challenges the traditional notion of multivessel status, prioritizing functionally optimal over angiographically complete revascularization.Methods: A retrospective analysis of patients with multivessel CAD admitted between January 2006 and December 2010 was conducted. Inclusion criteria comprised significant stenosis in at least two major coronary arteries, while those with prior CABG or angioplasty were excluded. Patient demographics, angiographic findings, and clinical outcomes were collected via phone interviews, medical records, and consultation.Results: Key cardiac events during follow-up included all-cause mortality, recurrent revascularization (surgical or percutaneous), myocardial infarction (with or without Q wave), and cerebrovascular accident (CVA).Conclusion: The study aims to provide insights into the efficacy and safety of coronary angioplasty as a treatment option for patients with multivessel CAD in real-world settings